Investigation on the growth, characterization and computational analysis of 2-Amino-2-thiazoline single crystals - H. Jude Leonard Hilary; P.C. Jobe Prabakar; G. Vijayakumar; S.G. Rejith; J. Divya; V. Sathana (Chemical Physics Impact, 2023)
By adapting the slow evaporation techniquethe titled compound 2-Amino-2-thiazoline (AMTZ) has been synthesized. The structural parameters of the crystal was studied by using single crystal X-ray diffraction method.Without the deposition of secondary phases, crystallite nature of the sample has been confirmed by analyzing powder X-ray diffraction method. From UV–visible spectrum study, the cut off wavelength was perceived at 285 nm & its optical constants has been calculated.Up to 128 °C, the thermal constancy of the sample was maintained & it reveals the durability of the crystal. The scanning electron microscope investigation has been carried out to decisive the surface morphology of the synthesized crystal. The mechanical roughness of the crystal has been characterized by Vickers's micro hardness test. It has been reported, that the variations in dielectric constant and loss for frequencies and temperature were observed for AMTZ crystals. By adapting Kurtz Perry Powder technique the second harmonic generation (SHG) efficiency was confirmed. By utilizing09W program package, B3LYP/6–311++G(d, p) method was adopted &the optimization of the structure was carried outto calculate the donor accepter interaction energy.The Time-Dependent Density Functional Theory (TD-DFT) was used to compute the electronic level of transition.